2731 Numaralı irade kayıt defteri (II. Abdülhamid dönemi) - Karataş, Üzeyir (My University, 2007)
Üzerinde çalıştığımız defter Sultan II. Abdülhamid devrine ait Hazîne-i Hâssa Nezâreti irâde kayıt defteridir. Defterde Hazine-i Hâssa Nezâreti’nin faaliyetleri hakkında bilgi verilmektedir. Memurların maaşlarından nişan ve madalya tevcihine, Hereke Fabrikası’ndan Osmanlı memleketinin dört bir tarafına yayılmış olan emlâk-i hümayun idarelerinin işleyişleri, varidat ve masarifatları, padişah tarafından yaptırılan hayır eserleri ile saray kasır köşk gibi saltanat ailesine münhasır binaların inşasından tamir ve tadiline kadar pek çok mevzuda malumat ve fikir verilmektedir.

The register book, which is the subject of this research, is the registration of commands of the Sultan about Hazîne-i Hâssa Ministry (the special ministry for the personal treasury of the Sultan) that belongs to Sultan II. Abdülhamid period. In the book (İrade kayıt defteri), various information and opinion about the operations of Hazîne-i Hâssa Ministry can be found; such as the salary of the government officials, bestowing the decorations or the medals on particular people, the operation of the Hereke factory and the management of the properties of the Sultan all around the country, incomes and costs, buildings and foundations built as a pious act by the Sultan and construction, renovation and restoration of the palace, pavilion and mansion buildings belong to the royal family.
Keywords: Maliye_Türkiye_Osmanlı İmparatorluğu; Maliye_Türkiye_Tarih; Türkiye_Tarih_Osmanlı İmparatorluğu, 1299-1918